Evaluation of tropical pasture legumes for fodder banks in subhumid Nigeria. 2. Accessions of Aeschynomene histrix, Centrosema acutifolium, C. pascuorum, Stylosanthes guianensis and S. hamata - Peters, Michael; Tarawali, Shirley A.; Alkamper, J. (1994)
Five accessions, comprising Aeschynomene histrix, Centrosema acutifolium, Centrosema pascuorum and Stylosanthes guianensis together with Stylosanthes hamata cVerano were evaluated over 2 years for use in fodder banks in subhumid Nigeria. The most promising accession was A. histrix 112463 with yields of more than 6 t/ha dry matter (DM) in the second growing season, good drought tolerance, ability to compete with the native vegetation and high nutritive value. C. pascuorum cCavalcade and C. acutifolium cv Vichada did not persist in competition with the native vegetation. At the end of the wet season, crude protein concentrations (whole plant) ranged from 10-17 percent DM and phosphorus concentrations from 0.08-0.19 percent DM. A. histrix fell in the middle of the range. This species should be evaluated along with other promising accessions in pasture mixtures in the region.